FSCIT's meeting room and tutorial room reservation and management system - Tang, Pei Pei (Universiti Malaysia Sarawak, (UNIMAS), 2014)
Like other University, their study room has its own room reservation system to deal the reservation room. It allows applying for the FCSIT tutorial room. Faculty Computer Science and Information Technology have ten tutorial rooms and each room has its own timeslot for the lecture time and activity. Beside each of the tutorial room is including facilities such projector, chair, whiteboard, desktop, speaker, and air-conditioner. It is a good learning environment for student and a place for activity such as presentation soft skill and other activity that involve the faculty activity. Besides, meeting room also required the reservation system. There consist three meeting room in FSCIT. Since some of the problem that occurs, the project is developing to let lecturer able to reserve the room and let the administrative to manage the system. Through this, lecturer allow to choose the time slot that prefer and reserve the room they prefer to run their event such as lecture, meeting, soft skill and tutorial section. The purpose of this system to make convenient to administrative in way their manage the room. In tradition way, administrative are follow up each lecturer schedule by phone call one by one. With this system, lecturer can reserve by them self.